2016
DOI: 10.1021/acs.bioconjchem.6b00013
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Peptide Nucleic Acid–Antimicrobial Peptide (PNA–AMP) Conjugates: Antisense Targeting of Fatty Acid Biosynthesis

Abstract: Antisense peptide nucleic acid (PNA) oligomers constitute a novel class of potential antibiotics that inhibit bacterial growth via specific knockdown of essential gene expression. However, discovery of efficient, nontoxic delivery vehicles for such PNA oligomers has remained a challenge. In the present study we show that antimicrobial peptides (AMPs) with an intracellular mode of action can be efficient vehicles for bacterial delivery of an antibacterial PNA targeting the essential acpP gene. The results demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 44 publications
1
54
0
Order By: Relevance
“…Hansen et al [166] reported that AMPs are efficient vehicles for the bacterial delivery of antibacterial antisense peptide-peptide nucleic acid (PNA) oligomers, which target the essential acpP gene. Hansen et al [166] reported that AMPs are efficient vehicles for the bacterial delivery of antibacterial antisense peptide-peptide nucleic acid (PNA) oligomers, which target the essential acpP gene.…”
Section: Other Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hansen et al [166] reported that AMPs are efficient vehicles for the bacterial delivery of antibacterial antisense peptide-peptide nucleic acid (PNA) oligomers, which target the essential acpP gene. Hansen et al [166] reported that AMPs are efficient vehicles for the bacterial delivery of antibacterial antisense peptide-peptide nucleic acid (PNA) oligomers, which target the essential acpP gene.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Hansen et al [166] reported that AMPs are efficient vehicles for the bacterial delivery of antibacterial antisense peptide-peptide nucleic acid (PNA) oligomers, which target the essential acpP gene. [166] Otvos et al [149] reported the dimeric analogue of prolinerich peptides in the form of pyrrhocoricin, which was able to deliver peptide antigens (NPK d epitope) into human fibroblast or dendritic cells (pyrrhocoricin-based epitope delivery system). Despite the fact that antisense antibacterial therapies have the potential to selectively kill bacteria, a major drawback to their development is that free oligonucleotides are poorly uptaken by bacteria.…”
Section: Other Applicationsmentioning
confidence: 99%
“…Antisense peptide nucleic acids (APNAs) could also be effectively used to restore vulnerability to β-lactams in methicillin-resistant Staphylococcus aureus and Staphylococcus pseudintermedius (Goh et al, 2015). It was also shown that APNA conjugated with antimicrobial peptides could effectively target acpP gene (responsible for growth of fatty acid chain in the biosynthesis of fatty acid) in E. coli with MIC values of 2-4 μM (Hansen et al, 2016). The ability of APNAs conjugated to the (KFF) 3 K CPP in Salmonella enterica serovar Typhimurium was explored to target possible essential genes (ligA, rpoA, rpoD, engA, tsf, and kdtA).…”
Section: -Thioguaninementioning
confidence: 99%
“…Antisense bacterial studies have principally relied upon covalent conjugation of the molecules to arginine-rich cellpenetrating peptides to achieve entry into bacteria. Previous publications [13][14][15][16][17] suggest that this approach may be more effective in gram-negative species, with fewer reports of successful treatment of gram-positive organisms and with no reports of successful treatment of C. difficile. 18 We recently presented our initial work investigating the use of cell-penetrating peptides to deliver antisense morpholinos into C. difficile.…”
Section: Introductionmentioning
confidence: 99%